Adoption of improved cookstoves in the peri-urban areas of Nairobi: Case of Magina area, Kiambu county, Kenya (Journal of Sustainability, Environment and Peace, 2019)
Concerted efforts have been made to enable communication and adoption of improved cookstoves by diverse development organizations in Kenya. However, their adoption remains low. This study sought to examine levels of adoption and use of improved cookstoves in Magina, Kiambu County and determine factors affecting their adoption and use. Results demonstrate that 93% of the households received the cookstoves from developmental programmes, among these 50% were making use of them but only 14% of the 50% had fully adopted them as main cookstoves. Efficiency and suitability, socio-cultural practices, economic capacity, limited capacity to appreciate the improved cookstoves concept and governance considerations were the cited limiting factors to adoption and use. There is need for an enabling policy and strategies to implement the bottom-up approach in the design and implementation of improved cookstoves to facilitate the upscaling of the adoption and use of improved cookstoves to conserve the forests in the country for sustainable development.
Keywords: Adoption, use, development organizations, dissemination, improved cookstoves